Irishness, Identity and Trauma in John McGahern’s Amongst Women (1990), Seamus Deane’s Reading in the Dark (1996), Sebastian Barry’s The Secret Scripture (2008) and Anne Enright’s The Gathering (2007) - BENHMEIDA, Mohamed Ala Eddine (l’Université de Mostaganem, 2022)
This thesis focuses on Irish identity and trauma representation in four contemporary Irish works, selected on their historical settings which are highly significant to the discussion. When read altogether, as a sequential historical representation of Ireland, these stories sculpt a multitude of social, political, and religious interpretations of what it means to be Irish during two pivotal periods in Irish history, notably from the War of Independence in the 1920s to the Celtic Tiger economic boom in the 1990s. Despite differences in themes, characters, and settings, these novels, namely John McGahern’s Amongst Women (1991), Seamus Deane’s Reading in the Dark (1996), Sebastian Barry’s The Secret Scripture (2008), and Enright Anne’s The Gathering (2006), depict their protagonists as singularities of Irish expression that had either been unheeded in Irish Literary Revival portrayals or had been unacknowledged by official national documents. Therefore, this thesis attempts to delve into the question of Irishness as a traumatic representation that has been, and continues to be, obscured by the centrality of national identifications and historical interpretations.However, because the identities of these protagonists are replete with haunting experiences that bear cultural multigenerational attributes, our enquiry takes a psychoanalytic approach by delving into trauma theory. The central argument is that each of these stories represents a distinct narrative, a facet of Irish history, and a collective experience. These narratives confront the promoted oneness of Irish national narratives and advance a transformation towards singularities of Irish expression that can only be communicated by conceptualising what traumatic memories entail.
Keywords: Irishness, Trauma, Multigenerational Trauma,Nationalism, Irish Traditional Paradigms, Irish Literary Rivals, John McGahern, Seamus Deane, Sebastian Barry, Anne Enright